Synthesis and characterization of novel dual-capped Zn–urea nanofertilizers and application in nutrient delivery in wheat. Issue 1 (20th January 2022) - Dimkpa, Christian O.; Campos, Maria G. N.; Fugice, Job; Glass, Katherine; Ozcan, Ali; Huang, Ziyang; Singh, Upendra; Santra, Swadeshmukul
Abstract : Nanoscale nutrients are promising for improving crop performance. Abstract : Nanoscale nutrients are promising for improving crop performance. However, size-induced potential for drifting, segregation, or transformation warrants strategies to streamline fertilization regimes. Herein, we developed three nanofertilizers by coating urea granules with Zn nanoparticles capped with binary capping agents: N -acetyl cysteine (NAC) and sodium salicylate (SAL); NAC and urea; or SAL and urea. Coating was accomplished at 80–100% efficiencies. When evaluated in sorghum through soil application at 6.4 (rate-1) and 2.1 (rate-2) mg Zn per kg soil, the nanofertilizers influenced sorghum performance, plant accumulation, and soil retention of Zn, N, and P comparably with the control (Zn-sulfate). However, SAL–urea–Zn, NAC–SAL–Zn, and NAC–urea–Zn nanofertilizers evoked rate-dependent significant ( P < 0.05) effects compared to Zn-sulfate. Early SPAD (chlorophyll) counts were significant with SAL–urea–Zn rate-1, compared to Zn-sulfate. NAC–SAL–Zn and SAL–urea–Zn rate-1 significantly increased shoot biomass, compared to Zn-sulfate. Notably, NAC–urea–Zn rate-2 strongly promoted grain or total above-ground Zn or N accumulation compared to SAL–urea–Zn rate-1, NAC–SAL–Zn rate-1, or NAC–urea–Zn rate-1, indicating that a lower rate of Zn can be used for NAC–urea–Zn to facilitate Zn and N delivery. Residual soil Zn was significantly higher with NAC–SAL–Zn rate-1, compared to Zn-sulfate. However, residual ammonium was significantly higher in Zn-sulfate, compared to other treatments, except for NAC–urea–Zn rate-2. Contrarily, residual P was significantly higher with SAL–urea–Zn rate-1 than with Zn-sulfate. These findings indicate that coating of urea with Zn nanoparticles can facilitate the application of nanoscale nutrients in agriculture, without any penalty on plant performance or nutrient delivery.